The Content Of Heavy Metal In Turmeric (Curcuma Domestica Val.) In The Volcanic Rocks Oligocene-Miocene Volcano, Biting Wonogiri, Central Java, Indonesia - Yudiantoro, Dwi Fitri; Soesilo, Joko; Basuki Rahmad; Haty, Intan Paramita; Radityo Prakoso; Muhammad Nurcholis; Mirzam Abdurrachman; Wikaningrum, Temmy (UIR PRESS, 2024)
The Biting Wonogiri area is an area composed of Oligocene-Miocene volcanic deposits and volcanic deposits from Lawu Volcano. The rocks in this area consist of pyroclastic rocks, volcanic breccia, and dacite intrusions. Residents in this area more commonly grow herbal plants such as turmeric. Turmeric plants are mostly planted on old volcanic rocks, namely the Oligocene-Miocene age. By studying the planting patterns of residents, an analysis was carried out regarding the heavy metal chemical elements contained in turmeric. The research methodology was carried out using geological mapping to determine the distribution of the rocks that make up the research area and AAS analysis (Atomic Absorption Spectroscopy). This AAS method is used to determine heavy metal content. The heavy metal elements analyzed in turmeric were Hg, Pb, As, Fe, Al, and Mn. From the analysis results it was found that the heavy metal elements Hg, Pb, and As had very low levels, namely around 0.005-0.400 mg/Kg. Meanwhile, the elements Al, Fe, and Mg have high contents. Turmeric grown on dacite and volcanic breccia has higher Al (622.3-1362.76 mg/Kg) and Fe (271.32-806.27 mg/Kg) content compared to turmeric planted on sedimentary rock. Meanwhile, the metal element Mn varies around 6.85-122.01 mg/Kg. By knowing the content of these Western metal elements, it is hoped that turmeric, which contains heavy metal elements, can be used as a superior herbal herbal medicine. These metal elements, which are very important nutrients, come from old volcanic rocks.